Biotechnology: Lifeline for endangered biodiversity (2018)
Recent threats to species and ecosystems are the greatest recorded in recent history. In the face of our ever-changing environment, the threshold for the conservation of biodiversity must be raised. A possible viable method is the use of biotechnology in the conservation efforts. This review therefore highlights the use of biotechnology to conserve, maintain and enhance biodiversity. Biotechnology is any technique that uses living organisms, or substances to make or modify a product, to improve plants or animals, or to develop microorganisms for specific uses. Biotechnology has been used to improve and enhance animal and crop productivity, as well as to conserve, evaluate and utilize various aspects of biodiversity. Several biotechnological approaches are important to conserve, analyze and detect genetic diversity of rare and endangered plants and animals. Cloning, plant tissue culture, transgenesis and cryopreservation are quite advantageous and a useful technique that has served to conserve biodiversity. Biotechnological approach, though expensive, can be helpful in the conservation of biodiversity, including threatened, endangered and critically endangered species.